A Lung Cancer Patient Harboring a Rare Oncogenic EGFR Exon 20 V786M Mutation Responded to a Third-Generation Tyrosine Kinase Inhibitor: Case Report and Review of the Literature - Zhu, Qi; Jiang, Mingyun; Li, Wenfei; Sun, Shuangli; Li, Jisheng; Stebbing, Justin; Liang, Xiaodong; Peng, Ling (Frontiers in Oncology, 2022)
Background: Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) are effective treatments for non-small cell lung cancer (NSCLC) patients with activating EGFR mutations. There are many uncommon and rare mutations in the EGFR gene. The efficacy of the EGFR-TKIs is largely unknown for cancers harboring uncommon or rare EGFR mutations. Case presentation: A 69-year-old woman was diagnosed with adenocarcinoma cT4N2M1c, stage IVB. Next-generation sequencing (NGS) confirmed a rare EGFR V786M mutation. During chemotherapy, immune checkpoint inhibitor (ICI) and anti-angiogenic treatment, no radiological response was observed. Subsequent third generation EGFR TKI showed a remarkable therapeutic effect. Structural prediction revealed the V786M mutation induces conformational change at the dimer interface, without altering the ATP binding to EGFR tyrosine kinase domain (TKD). Consistently, docking simulations indicated that the affinity of ATP to the V786M mutant was not disturbed, which explained the TKI sensitivity. Conclusions: Our data confirmed the activating role on EGFR V786M mutation. Together with structural predictions and clinical evidence for activity of TKIs against EGFR V786M mutations, these findings warrant further investigation.